COHESIVE DEVICES IN JOURNALISTIC ARTICLES AND CHILDREN STORY - Putu Nur Ayomi (SPHOTA: Jurnal Linguistik dan Sastra, 2020)
ABSTRACT This study attempts to describe the characteristic of cohesive devices used in journalistic texts and children stories. In language learning, it will be beneficial for students to be able to relate the characteristics of the language in use and the function it performs. The quantitative and qualitative analyses were applied in analysing the sample texts; two travel articles taken from magazine and two fables. The finding suggests that personal references tend to be more varied and more dominant in children stories as they are applied to trace characters throughout the story. Demonstrative pronouns are used more frequently in travel articles to refer to places and events. The use of lexical cohesion shows that repetition of the characters’ name occurs significantly in fables; meanwhile the travel articles use more synonymy and meronymy. Collocation plays important role to build discourse unity in both genres. However, it is more topic related rather than genre related. Keywords: cohesive devices, travel article, children story